The impact of the crisis on the SME sector in Romania-The back-up of innovation and entrepreneurship development - Zsuzsanna K.SZABO (Revista Romana de Economie, 2011)
It is widely recognized that the economic recovery largely depends on the improvement of the SME sector. In the order to determine the opportunities and to analyze the challenges faced by Romanian SMEs in (post)crises period, the paper presents first a short review of the national economy and the role of the SME sector. The paper presents also the situation of the SME sector after 2008 and a SWOT analysis in order to identify targets for the next period in concordance with the Europe 2020 strategy.